Autofabulação... O sensível e o imaginário social: sentires na formação de professores - Santos, Camila Borges (2020)
This doctoral thesis work in Education was developed in Research Line 1 - Training, Knowledge and Professional Development, of the Graduate Program in Education, at the Federal University of Santa Maria (UFSM). Her investigation is based on my personal and professional trajectory as an actress-teacher, due to concerns related to teacher training and driven by research carried out with the Group of Studies and Research in Education and Social Imagery - GEPEIS. The themes of Sensitive and Social Imaginary, more than being linked to my education and my profession, are connected to the things that cause me to think about life. As an excerpt of this study, I chose to work with the Pedagogy and Theater Degree courses at UFSM, due to the approach I have with these two courses, both as a student and as a teacher, and also for affection. In the face of some concerns, such as: how we produce knowledge; in what ways are the formative processes developed, which generate the theme of the sensitive in this research, I bring the following problem: how is the sensitive mobilized in the training of teachers in the Degree in Pedagogy and Degree in Theater at UFSM? I present as a general objective, the will to understand the processes of mobilization of the sensible in the formation of teachers in the Courses of Pedagogy and Degree in Theater. The theoretical contribution is from the Social Imaginary, by Cornelius Castoriadis (1982), from the Sensitive, from Michel Maffesoli (1998), from the Aesthetic Experience, from Nadja Hermann (2005), from the Autobiography, from Marie-Chistine Josso (2010) and da Neuroscience, with António Damásio (2017). The methodology was created especially for this investigation, entitled Self-fabulation, defined as: invented narrative of yourself, through the imaginary creation of facts and actions of your life or your training. The teachers in training collaborated in the methodological process, making it possible to meet in three essays and making the autobiographical reports, the autofabulations and the conversation circles about the sensitive viable, for the production of the data of this research. I therefore point out, as a thesis: the sensitive is a knowledge for the teaching profession, mobilized by the aesthetic experience in teacher education, by the teaching practices in the Teaching and Teaching Degree Courses in Theater. The sensitive is a knowledge first linked to the senses of the body and the ability to feel the world with meaning. This research also showed, from the production of creative writing and conversation circles, that experience is an important means, through which we learn and that the body is a participant in the construction of knowledge. We can thus turn our attention to this issue in the training of teachers, expanding the understanding and practice of the sensitive in the formative processes.